The Economic Well-Being of Women Who Become Divorced or Separated in Mid and Later Life - Webb, Sharon C. (My University, 1999)
The aging of the baby boom and rising divorce rates mean that many women will spend their later life without income from a husband. Using 1994 data from the Statistics Canada Survey of Labour and Income Dynamics, this thesis examines the economic well-being of women who become divorced or separated in mid and later life. Means and chi-square tests are used to compare the various demographic income and employment characteristics of women and men aged 45 and older in their first marriages to women and men who become divorced or separated at age 45 and older. Linear and logistic multiple regression analyses are performed to examine factors associated with the economic well-being of older women. Economic well-being is measured by three variables: adjusted economic family total money income; before-tax low income cutoff; and ownership of dwelling. Results of this study show that women who become divorced or separated in mid and later life are much more likely to be in poverty than married men, married women and men who divorce or separate in mid and later life. This is particularly pronounced for women aged 65 and older who become divorced or separated at age 45 and older. Results also show that persons who divorce or separate in mid and later life are less likely than married persons to live in a dwelling which is owned by a member of the household. Factors which are positively associated with income for women who become divorced or separated in mid and later life include: receiving investment income; receiving earnings; receiving pension income; and years of schooling. For female paid workers who become divorced or separated in mid and later life, the total number of hours paid and being a professional are associated with higher income. Very few women in this study received alimony and it was not found to be associated with income for women who become divorced or separated in mid and later life. Results of this study are consistent with previous research which shows extremely high rates of poverty among unmarried older women. These findings indicate that significant reforms are needed for the Canadian legal and retirement income systems in order to improve the economic well-being of women who divorce or separate in mid and later life. Policy implications and recommendations for future research are discussed.
Keywords: Sociology; Sociology